Si Bolang Game Raises Gross Motor Skills in Early Childhood: Permainan Si Bolang Meningkatkan Keterampilan Motorik Kasar pada Anak Usia Dini - Siti Mutamimah Alfiah; Choirun Nisak Aulina (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Gross motor development is a fundamental aspect of early childhood growth, enabling children to perform coordinated physical activities involving large muscle groups. Specific Background: Many children aged 3–4 years at KB Al-Faqih demonstrated inadequate gross motor abilities, such as difficulties in running, jumping, balancing, and coordinating movements during daily activities. Knowledge Gap: Existing classroom practices relied heavily on visual instruction with limited direct physical engagement, leaving a need for structured, play-based interventions that actively stimulate large-muscle movement. Aims: This study aimed to increase the gross motor skills of children aged 3–4 years through the Si Bolang obstacle-based game using a Classroom Action Research design with two cycles. Results: Baseline observation showed a low achievement level of 41.91%, which rose to 60.29% in Cycle I and reached 82.72% in Cycle II after revising the game with a competitive two-track format. Improvements were observed across coordination, agility, balance, and strength indicators. Novelty: The study introduces a modified obstacle game incorporating treasure rewards and progressive gameplay adjustments as a structured learning medium for very young children. Implications: Findings suggest that well-designed physical play integrated into classroom activities can serve as a practical strategy for stimulating motor development and increasing children’s participation in early childhood education settings. Highlights: Performance rose markedly from baseline to the second intervention cycle. Competitive dual-track gameplay generated stronger engagement during activities. Movement tasks improved coordination, agility, balance, and strength simultaneously. Keywords:Gross Motor Skills; Early Childhood Education; Obstacle Game; Classroom Action Research; Physical Play